2015
DOI: 10.5195/ijms.2015.263
|View full text |Cite
|
Sign up to set email alerts
|

Lifesaving Sonography Protocols: A Pilot Course Involving Undergraduate Medical Students

Abstract: Background: Ultrasonography protocols are easy to learn, frequently used in emergency medicine, and could be useful for inexperienced doctors. Inthis field, only a few protocols are needed to give an initial diagnosis and to start fast and proper treatment. Until now, only Focused Assessmentwith Sonography for Trauma (FAST) protocol training studies have been reported in the medical literature. Our point-of-care course, comprisedof extended FAST, lung scan and ocular scan trainings. The students’ curriculum us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…When surveyed, the students assessed ultrasound training favorably, and were in favor of further training with this modality (Gogalniceanu et al, ). At the University of Gdansk, Poland, a medical school class was provided an intensive six‐day US course, with 22 hours of lectures and 18 hours of hands‐on training exercises (Wisniewski and Garnier, ). Subsequent scores on a practical examination related to US imaging of the lungs, cardiovascular system and eyes increased significantly, and 96% of students were able to perform a standardized FAST examination in less than two minutes (Wisniewski and Garnier, ).…”
Section: Ultrasonography In Graduate Medical Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…When surveyed, the students assessed ultrasound training favorably, and were in favor of further training with this modality (Gogalniceanu et al, ). At the University of Gdansk, Poland, a medical school class was provided an intensive six‐day US course, with 22 hours of lectures and 18 hours of hands‐on training exercises (Wisniewski and Garnier, ). Subsequent scores on a practical examination related to US imaging of the lungs, cardiovascular system and eyes increased significantly, and 96% of students were able to perform a standardized FAST examination in less than two minutes (Wisniewski and Garnier, ).…”
Section: Ultrasonography In Graduate Medical Educationmentioning
confidence: 99%
“…At the University of Gdansk, Poland, a medical school class was provided an intensive six‐day US course, with 22 hours of lectures and 18 hours of hands‐on training exercises (Wisniewski and Garnier, ). Subsequent scores on a practical examination related to US imaging of the lungs, cardiovascular system and eyes increased significantly, and 96% of students were able to perform a standardized FAST examination in less than two minutes (Wisniewski and Garnier, ). Afonso et al () also integrated US instruction into a physical diagnosis course, with demonstrations followed by practice on standardized patients.…”
Section: Ultrasonography In Graduate Medical Educationmentioning
confidence: 99%
“…Blehar et al (2015) demonstrated that reliable ultrasound examinations need much experience, especially if the results are to be interpreted correctly. It has been proved that in many medical fields only a few protocols are needed for initial diagnosis and for starting the right treatment (Frederiksen et al, 2012;Wisniewski and Garnier, 2015), but ultrasonography is one of the easiest-tolearn radiological methods. Indeed, Chiao et al (2005) showed that ultrasonography is easy to teach to crew members of the International Space Station, who had no medical education.…”
Section: Dear Editormentioning
confidence: 99%
“…1 Ultrasound is now an essential part of undergraduate medical education. 2 , 3 Emergency ultrasound education, especially for the senior undergraduate years, may help students to use bedside ultrasound in their future management of critically-ill patients. Ultrasound is an essential tool for the diagnosis, resuscitation, and critical care of trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Assessments for EFAST training include pre and post-test, and psychomotor skill evaluation. 3 , 7 Objective structured clinical examination (OSCE) assessments were used by some researchers to better understand students' performance on EFAST. 6 To the best of our knowledge, the correlation between EFAST skills and other clinical skills (cardiopulmonary resuscitation, airway management, suturing, emergency case management) were not studied before.…”
Section: Introductionmentioning
confidence: 99%